A phase I/II dose-escalation study investigating all-oral ixazomib-melphalan-prednisone induction followed by single-agent ixazomib maintenance in transplant-ineligible newly diagnosed multiple myeloma - San-Miguel, Jesús F; Echeveste Gutierrez, Maria-Asunción; Špicka, Ivan; Mateos, María-Victoria; Song, Kevin; Craig, Michael D; Bladé, Joan; Hájek, Roman; Chen, Christine; Di Bacco, Alessandra; Estevam, Jose; Gupta, Neeraj; et al. (Haematologica, 2018)
This phase I/II dose-escalation study investigated the all-oral ixazomib-melphalan-prednisone regimen, followed by single-agent ixazomib maintenance, in elderly, transplant-ineligible patients with newly diagnosed multiple myeloma. Primary phase I objectives were to determine the safety and recommended phase II dose of ixazomib-melphalan-prednisone. The primary phase II objective was to determine the complete plus very good partial response rate. In phase I, patients were enrolled to 4 arms investigating weekly or twice-weekly ixazomib (13 28-day cycles or nine 42-day cycles) plus melphalan-prednisone. In phase II, an expansion cohort was enrolled at the recommended phase II ixazomib dose. Of the 61 patients enrolled, 26 received the recommended phase II dose (ixazomib 4.0 mg [days 1, 8, 15] plus melphalan-prednisone 60 mg/m2 [days 1-4], 28-day cycles). Of the 61 enrolled patients, 36 (13 of 26 in the recommended phase II dose cohort) received single-agent ixazomib maintenance (days 1, 8, 15; 28-day cycles). In phase I, 10/38 patients reported dose-limiting toxicities in cycle 1, including grade 3 and/or 4 neutropenia (n=6) and thrombocytopenia (n=4). Complete plus very good partial response rate was 48% (48% at recommended phase II dose), including 28% (22%) complete response or better; responses deepened during maintenance in 34% (33%) of evaluable patients. After median follow up of 43.6 months, median progression-free survival was 22.1 months. Adverse events were mainly hematologic events, gastrointestinal events, and peripheral neuropathy. This study demonstrates the feasibility, tolerability, and activity of ixazomib-melphalan-prednisone induction and single-agent ixazomib maintenance in transplant-ineligible newly diagnosed multiple myeloma patients. clinicaltrials.gov identifier 01335685.
Keywords: glycin; udržovací chemoterapie; Melphalan; metastázy nádorů; Kaplan-Meier Estimate; prednison; Female; výsledek terapie; ženské pohlaví; Kaplanův-Meierův odhad; lidé; staging nádorů; mnohočetný myelom; Prednisone; Aged, 80 and over; Boron Compounds; Induction Chemotherapy; Antineoplastic Combined Chemotherapy Protocols; Treatment Outcome; protokoly protinádorové kombinované chemoterapie; indukční chemoterapie; melfalan; Male; Aged; aplikace orální; Glycine; lidé středního věku; senioři nad 80 let; Multiple Myeloma; senioři; mužské pohlaví; Administration, Oral; Neoplasm Metastasis; sloučeniny boru; Middle Aged; Neoplasm Staging; Maintenance Chemotherapy; Humans